2019
DOI: 10.1088/1361-6587/ab52a4
|View full text |Cite
|
Sign up to set email alerts
|

Pushing microscopic matter in plasma with an electron beam

Abstract: Manipulation of microscopic structures is routinely carried out by exploiting the light pressure of a focused laser beam. Here we use a pulsed electron beam (EB) with energy 10-14 keV and peak current 4 mA instead of a photon flux and demonstrate transport of microscopic matter over a few centimeters. Hundreds of electrically charged microspheres m 11.8 m in diameter immersed in a radio-frequency plasma are driven into a flow with a speed of a few mm s −1 when irradiated by the EB. It is shown that the force a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…These previous studies, using Newton-Cotes rules for numerical integration, have shown that the linear momentum transferred to an aluminum or gold NP is predominantly attractive towards the swift electron trajectory but becomes repulsive at small impact parameters [26][27][28][29]. This is in qualitative agreement with what has been experimentally observed [10][11][12][13][14][15][16][17]. However, it has been suggested that the dielectric function used in the linear momentum transfer calculations for the gold NP may have lead to non-causal unphysical results [30], because it was obtained from the interpolation and extrapolation of data, collected from different experiments (with different samples) and carried out for different frequency ranges, compiled by Palik [31].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…These previous studies, using Newton-Cotes rules for numerical integration, have shown that the linear momentum transferred to an aluminum or gold NP is predominantly attractive towards the swift electron trajectory but becomes repulsive at small impact parameters [26][27][28][29]. This is in qualitative agreement with what has been experimentally observed [10][11][12][13][14][15][16][17]. However, it has been suggested that the dielectric function used in the linear momentum transfer calculations for the gold NP may have lead to non-causal unphysical results [30], because it was obtained from the interpolation and extrapolation of data, collected from different experiments (with different samples) and carried out for different frequency ranges, compiled by Palik [31].…”
Section: Introductionsupporting
confidence: 87%
“…The manipulation of micro-and nano-objects has been a field of interest since the second half of the last century given its potential applications for new technologies [1][2][3][4][5][6][7][8]. In particular, it has been experimentally observed that the Transmission Electron Microscope (TEM) can be used as a tool to induce movement on nanoparticles (NPs) due to forces of attraction or repulsion towards the electron beam [9][10][11][12][13][14][15][16][17]. In this direction, Scanning Transmission Electron Microscopes (STEMs) are promising instruments for nanomanipulation due to constant improvements in both spatial [18][19][20][21][22] and spectral [23][24][25] resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we calculate the total linear momentum lost by the swift electron and transferred to the NP by integrating numerically the forces [Eqs. ( 6) and ( 7)], obtaining that ∆ P e + ∆ P = 0 (16) for both aluminum and gold NPs. Thus, the total linear momentum gained by the NP is precisely the same that the linear momentum lost by the swift electron.…”
Section: Radiation Emitted By the Nanoparticle And Conservation Of Li...mentioning
confidence: 99%
“…3,7,8 In this electromagnetic context, electron beams produced in transmission electron microscopes (TEM) have also shown to be potentially useful probes for guiding the motion of nanoparticles (NPs). [9][10][11][12][13][14][15][16] In previous works it was demonstrated that electron beams are capable to induce coalescence in separated nanoscale metal particles. [9][10][11][12] Interestingly, the recent ability to achieve sub-angstrom resolution in the aberration-corrected scanning transmission electron microscopes (STEM), [17][18][19][20][21] and the parallel efforts to push the spectral resolution in the range of millielectronvolts, [22][23][24] make STEM an attractive alternative tool for nanomanipulation with high spatial and spectral resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the motion of swimming and flying animals [1], growth of stalagmites [2], fall motion of hailstones [3], motion of pollutants in the atmosphere [7], complex motion of the drill string in the field of petroleum engineering [8], and flow over bridge piers, chimney stacks, offshore structures, and tower structures in civil engineering [9], aircrafts in the field of aerospace [10], nuclear fuel rods in the atomic field [5], power battery cooling structures in the field of new energy vehicles [11], heat exchanger tubes in thermal engineering [12], etc. The fluid dynamic drag [13][14][15], active and passive methods for drag reduction [16][17][18], boundary layer flow [19], flow-induced vibration [5], behavior of turbulent fluid motion [20], and instability in the wake shear layer [21][22][23] are of interest in numerous fields. Owing to its practical importance in engineering applications and theoretical significance in understanding fundamental fluid mechanics, the flow over a circular cylinder has attracted extensive study interest from both scientists and engineers.…”
Section: Introductionmentioning
confidence: 99%